Sign language ideologies in practice - Green, Mara; Kusters, Annelies; Moriarty, Erin; Snoddon, Kristin (Sign languages and deaf communities ;, 2020)
This book focuses on how sign language ideologies influence, manifest in, and are challenged by communicative practices. Sign languages are minority languages using the visual-gestural and tactile modalities, whose affordances are very different from those of spoken languages using the auditory-oral modality.